Faktor-faktor yang mempengaruhi perilaku konsumen terhadap keputusan pembelian hijab pada santriwati Dayah Darul Mua'rif Al-Azizizyah - Qudratul Munira (el-Amwal, 2021)
This study aims to determine the factors influencing consumer behavior towards the purchase decisions of Hijab among Dayah students of Darul Mua'rif Al-Aziziyah. This study uses primary data obtained by distributing questionnaires to 61 respondents selected using the Slovin formula. The data analysis method used is multiple linear regression with the help of SPSS. The results partially show that culture has a positive but insignificant effect on purchase decisions of Hijab at the Dayah students of Darul Mua'rif Al-Aziziyah, social has a positive and significant effect on purchase decisions of Hijab at the Dayah students of Darul Mua'rif Al-Aziziyah, person has a negative and insignificant effect on purchase decisions of Hijab at the Dayah students of Darul Mua'rif Al-Aziziyah, psychology has a positive and significant effect on purchase decisions of Hijab at the Dayah students of Darul Mua'rif Al-Aziziyah, and design has a negative and insignificant effect on purchase decisions of Hijab at the Dayah students of Darul Mua'rif Al-Aziziyah. Simultaneously, culture, social, person, psychological, and design have a significant effect on the purchase decisions of Hijab at Dayah of Darul Mua'rif Al-Aziziyah.